2015
DOI: 10.18632/oncotarget.3691
|View full text |Cite
|
Sign up to set email alerts
|

EFEMP1 promotes the migration and invasion of osteosarcoma via MMP-2 with induction by AEG-1 via NF-κB signaling pathway

Abstract: The role of epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1) in osteosarcoma remains unknown. Then applying EFEMP1 siRNA, plasmids transfection and adding purified EFEMP1 protein in human osteosarcoma cell lines, and using immunohistochemistry on 113 osteosarcoma tissues, demonstrated that EFEMP1 was a poor prognostic indicator of osteosarcoma; EFEMP1 was specifically upregulated in osteosarcoma and associated with invasion and metastasis in vitro and in vivo. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 41 publications
7
41
0
Order By: Relevance
“…Through previous studies, we found that EFEMP1 was involved in the regulation of many biological processes in carcinoma, suggesting that EFEMP1 may play an important role in the development of HCC. When the transcription of EFEMP1 was inhibited, how did it cause phenotypic changes in HCC cells, and by what kind of signaling pathway to affect HCC?…”
Section: Resultsmentioning
confidence: 96%
“…Through previous studies, we found that EFEMP1 was involved in the regulation of many biological processes in carcinoma, suggesting that EFEMP1 may play an important role in the development of HCC. When the transcription of EFEMP1 was inhibited, how did it cause phenotypic changes in HCC cells, and by what kind of signaling pathway to affect HCC?…”
Section: Resultsmentioning
confidence: 96%
“…As a downstream target gene of Ha-ras and c-myc, AEG-1 mediats its tumor promoting effects [25]. Recent reports has shown that AEG-1 plays as a key converging point in oncogenic signaling pathways including the NF-kB pathway, the PI3K/AKT pathway, the Wnt pathway [9,26,27]. Through activating the nuclear factor kappaB (NF-kB) signaling pathway, AEG-1 induces increased anchorage-independent growth and invasiveness of tumor cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor‐containing fibulin‐like ECM protein 1 (EFEMP1, also called fibulin‐3) is reported to be upregulated in OS. The overexpression of EFEMP1 upregulates the expression of MMP‐2 and contributes to the migratory and invasive capability of OS cells by binding the EGF receptor and activating the MAPK and Akt pathways . Wang et al.…”
Section: Mmps Promote Osteosarcoma Progressionmentioning
confidence: 99%
“…also speculated that EFEMP1 is a downstream target molecule of astrocyte elevated gene‐1 (AEG‐1, also known as metadherin or lyric) that is highly expressed in OS. They considered that AEG‐1 mediates OS progression and metastasis through upregulating MMP‐2 expression via activation of EFEMP1 by NF‐κB signaling pathway . B7‐H3 is a member of the B7‐family of costimulatory molecules, which has been shown to promote OS cell invasion, at least in part by upregulating MMP‐2 .…”
Section: Mmps Promote Osteosarcoma Progressionmentioning
confidence: 99%